Impacts of Surgery on Symptom Burden and Quality of Life in Pituitary Tumor Patients in the Subacute Post-operative Period - Waddle, Mark R.; Oudenhoven, Mollie D.; Farin, Casey V.; Deal, Allison M.; Hoffman, Riane; Yang, Hojin; Peterson, Jennifer; Armstrong, Terri S.; Ewend, Matthew G.; Wu, Jing (Frontiers in Oncology, 2019)
Background: Pituitary tumors are rare but are associated with significant symptoms that impact patients’ quality of life (QOL). Surgery remains one of the most effective treatment options for long term disease control and symptom benefit, but symptom and quality of life recovery in the subacute period has not been previously reported. This study aimed to better understand the impact of surgery on patients’ symptom burden and QOL in the subacute post-surgical period. Methods: Twenty-three adult patients with pituitary tumors undergoing surgical resection at University of North Carolina Cancer Hospital were enrolled in this study. M.D. Anderson Symptom Inventory Brain Tumor Module, European Organization for Research and Treatment of Cancer QLQ-C30 and QLQ-BN20 questionnaires were collected pre- and one-month post- surgical resection and differences were analyzed for individual and groups of symptoms and QOL using Wilcoxon signed-rank tests. Results: Twenty adult patients had both pre-operation and post-operation follow-up visits; 60% had functional pituitary adenomas. Seven symptoms including fatigue, memory, vision, numbness, speaking, appearance, and weakness were significantly improved at the one-month post-operation visit while one symptom, sleep, worsened. Global Health Status/QOL measurements was improved minimally from 63 (SD 25) at pre-operation to 67 (SD 22) at one-month post-operation without statistical significance. Conclusions: This study demonstrated a rapid improvement of many symptoms in the subacute post-operative period in pituitary tumor patients. Disturbed sleep was identified as the only symptom to worsen post-operatively, encouraging potential prospective interventions to improve sleep and subsequently improve the QOL in pituitary tumor patients following surgical intervention.